Increased risk of rheumatoid arthritis in patients with endometriosis: genetic aspects. (8th March 2022) - Zervou, Maria I; Vlachakis, Dimitrios; Papageorgiou, Louis; Eliopoulos, Elias; Goulielmos, George N
Abstract: RA is an inflammatory joint disease of an autoimmune nature, with a complex mode of inheritance characterized by chronic and destructive inflammation in the peripheral joints of the hands and feet and irreversible disability. This disorder occurs more often in women, and reproductive and hormonal factors have been shown to be related to increased risk. Endometriosis is a chronic, complex, oestrogen-dependent and progressive gynaecological disorder characterized by the growth of endometrial tissue outside the uterine cavity. Thus far, substantial abnormalities in the immune system of women with endometriosis have been demonstrated. Epidemiological data have suggested a link between endometriosis and the risk of incident RA. The similarities between molecular and cellular pathways of endometriosis and RA may implicate a partially shared genetic background. In this review we present an overview of the shared genetic factors known thus far that are associated with the development of both disorders.